Macroscopic Diagnosis of Plant Diseases Caused by Pathogenic Microorganism - Annisyah Nasution; Vivi Mardina; Sara Gustia Wibowo (Serambi Journal of Agricultural Technology, 2021)
From a biological point of view, plant diseases are deviations from internal traits that cause plants to not be able to carry out normal growth activities. Plant diseases in the field can be identified based on signs and symptoms of diseases that appear. This study aims to determine how to diagnose macroscopically the symptoms of diseases that arise due to pathogenic microorganisms on plants. This research was conducted in 3 stages which included the location survey, observation, and primary data collection stages. The method for primary data collection is done by direct observation, namely direct observation of samples and documented. Data were analyzed using the formula to calculate the percentage and intensity of disease attacks on plants. The results obtained were as many as 3 plant species (Capsicum sp, Solanum escelentum, Oryza sativa) from 12 plants which were observed to be attacked by pathogenic microorganisms with a percentage amount (22,45 %, 58,97%, 9%). Obtain 4 types of pathogenic microorganisms that attack plants, namely Gemini virus that causes leaf curling in Capsicum sp plant, Pyricularia oryzae fungus which causes leaf blast in Oryza sativa plants, the fungus Alternaria solani causes dry spot and Rhizoctonia solani fungus which causes leaf blast in Oryza sativa plants, the fungus Alternaria solani causes leaf dry spot and Rhizoctonia solani fungi that cause fruit rot in Solanum escelentum.